OPTIMALISASI PENCAHAYAAN ALAMI GEDUNG PERPUSTAKAAN (STUDI KASUS: GEDUNG PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR) - Ismajaya, Muh. Aryanugraha; Nurul Jamala B; Asniawaty (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2023)
This research aims to optimize natural lighting in the Alauddin Makassar State Islamic University Library building by enhancing the distribution of natural light. The study employs a quantitative method involving direct measurement of natural lighting using a lux meter on-site and the dissemination of questionnaires among library visitors. Field measurement data is processed using MS Office Excel to assess the lighting conditions. Additionally, the application of Autodesk Ecotect with the Desktop Radiance plugin is utilized to simulate field measurement outcomes. To optimize natural lighting, simulations are conducted using six different models of light shelves. The simulation results indicate that employing a light shelf positioned centrally with an external angled surface proves most effective in maximizing natural light entry into the building. On the second floor, a centrally positioned light shelf with a 15° angle on each outer window opening yields the highest R2 value of 0.94. Meanwhile, on the third floor, using a centrally positioned light shelf with a 30° angle on the north side and 15° on the south side of the window achieves the highest R2 value of 0.85.